Successful outcome of placenta previa percreta with bladder invasion - Sayeeda, Syeda; Akhter, Nahreen; Begum, Firoza; Hasan, Sajid (Bangabandhu Sheikh Mujib Medical University Journal, 2017)
A 41 year old multiparous lady, with previous history of one cesarean section presented at her 24 weeks of gestation with frank hematuria. The case was diagnosed as placenta previa percreta with the bladder involvement by ultrasound doppler and confirmed by MR urogram. So, peripartum hysterectomy was planned. On opening of the abdomen, a hugely distended bladder was found, which when retracted engorged blood vessels were found over the lower segment of uterus. Baby was delivered by giving a transverse incision in the upper segment. By keeping placenta in situ, total abdominal hysterectomy was done with quick successive clamping. Severe per-operative bleeding was occurred. Bladder irrigation started following total abdominal hysterectomy. Continuous small clots were coming out through catheter. A large old blood clot was removed by cystostomy done by an urologist. A sprouting vessel and a linear injury were noticed at the base of the bladder. The vessel was ligated and the injury was repaired. After proper hemostasis, the abdomen was closed in layers. The patient was shifted to ICU. Patient developed complications like MI, watery diarrhoea, low grade fever which was managed accordingly. She was discharged healthy on her 19th post-operative day.